Undergraduates’ Awareness of English Irregular Verbs - Harits Setyawan (TEKNOSASTIK, 2018)
The objectives of this research were to find out undergraduates’ awareness of English irregular verbs and to find out what errors that the students made in using the irregular verbs. This research was conducted at University of Teknokrat Indonesia. The population of this research was the first semester students. There were 30 university students who were chosen as the samples. They were all S1 English Literature students. The data of this research were collected through a written task. The task was designed to measure the students’ ability in using irregular verbs in sentences telling about past events. There were 140 irregular verbs tested to the students. The result of the research showed that the undergraduates’ awareness of English irregular verbs is low; 22 (73.3%) out 30 students made errors in using English irregular verbs. The errors varied into three types; using the rule of regular verbs for irregular verbs, using simple form verbs for past events, and creating new words which did not exist in English vocabulary. The highest number of error was placed by applying the rule of regular verbs for irregular verbs with 14 incorrect verbs (53.8%), the second position was placed by using simple form verbs for past events with 9 incorrect verbs (34.6%), and the third position was placed by creating new words which did not exist in English vocabulary with 3 incorrect verbs (11.5%). The results of this study indicate that students in which English is a foreign language might still have insufficient English vocabulary when they come to higher schools.Keywords: Foreign language, error, irregular verb